(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the changed scenario, increase in the level of anxiety and depressive symptoms in adolescents may be due to social media use. In this background researcher intended to study that how social media use could cause in increasing anxiety and depressive symptoms in adolescents by using Descriptive survey research design. In this study, included 70 participants (late adolescents) residing in urban Bangalore set up, consisting of 35 boys and 35 girls. The required systematic data was gathered by using semi structured interview, anxiety scale (self-analysis form), Beck’s depression inventory and social networking status scale. From the results, it is found that there is no significant influence of social media use on the level of on anxiety and depressive symptoms among adolescents.